Amendments to the Modern Processual Form of Administrative Proceedings under Condition of Quarantine Caused by COVID-19 - Vovk, Pavlo V. (P.A. Persona e Amministrazione, 2022)
In modern realities the study of the processual form of administrative proceedings under quarantine caused by COVID-19 is important due to the increased need to protect the rights, freedoms and legitimate interests of individuals. The purpose of the study is to analyze the modern processual form of administrative proceedings and the compliance of law modifications with the quarantine conditions caused by COVID-19. The methodological basis of the study represents a set of updated methods of scientific research. The use of formal-logical and structural-functional methods allowed to highlight the elements of the processual form of administrative proceedings and to characterize the main aspects of their transformation, including processing in the quarantine period and restrictions caused by COVID-19. It is of interest to analyze the introduction of an electronic court, electronic exchange of processual documents, as well as participation in court sessions in the mode of the videoconference. With the help of the modeling method the disadvantages and risks of taking part in court sessions in the mode of the videoconference are highlighted. System analysis contributed to the consideration of the processual form as the most distinctive feature of administrative proceedings. The study revealed that the processual form of administrative proceedings had undergone particular fragmentary changes due to the test launch of individual subsystems of the Unified Judicial Information and Telecommunication System (UJITS) (as example: “E-Court”) and the introduction of taking part in court sessions in the mode of the videoconference. It has been found that in the present realities, the processual form of administrative court proceedings needs further modifications aimed at ensuring the flexibility and a high degree of adaptability of legislative assistance to new conditions of implementation, allowing to guarantee the observance and protection of the rights, freedoms and interests of citizens whenever previously used methods and mechanisms appear to be ineffective. However, the digitalization of the processual form of administrative proceedings cannot be considered the only panacea eliminating all inherent problems. The highlighted points of the study might improve the processual form of administrative proceedings, especially in the quarantine caused by COVID-19.